2011
DOI: 10.1038/nbt.1788
|View full text |Cite
|
Sign up to set email alerts
|

Generation of anterior foregut endoderm from human embryonic and induced pluripotent stem cells

Abstract: Directed differentiation of human embryonic stem (hES) cells and human induced pluripotent stem (hiPS) cells captures in vivo developmental pathways for specifying lineages in vitro, thus avoiding perturbation of the genome with exogenous genetic material. Thus far, derivation of endodermal lineages has focused predominantly on hepatocytes, pancreatic endocrine cells and intestinal cells1–5. The ability to differentiate pluripotent cells into anterior foregut endoderm (AFE) derivatives would expand their utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
424
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(444 citation statements)
references
References 31 publications
17
424
3
Order By: Relevance
“…As ZIKV also targets human neuronal progenitor cells (hNPCs) and neurons [33][34][35][36], we further evaluated drug efficacy in the human induced pluripotent stem cell (iPSC) line HDF9 [37] and iPSC-derived hNPCs [38]. We found that all three drugs considerably reduced ZIKV titers in hNPCs and HDF9 iPSCs ( Figure 4D-4G).…”
Section: Inhibition Of Zikv In Human Stem Cells and Neural Progenitormentioning
confidence: 96%
See 1 more Smart Citation
“…As ZIKV also targets human neuronal progenitor cells (hNPCs) and neurons [33][34][35][36], we further evaluated drug efficacy in the human induced pluripotent stem cell (iPSC) line HDF9 [37] and iPSC-derived hNPCs [38]. We found that all three drugs considerably reduced ZIKV titers in hNPCs and HDF9 iPSCs ( Figure 4D-4G).…”
Section: Inhibition Of Zikv In Human Stem Cells and Neural Progenitormentioning
confidence: 96%
“…The human iPS cell line IPSC-HDF9 [37] was cultured and maintained on pre-coated matrigel (BD Biosciences) plates and fed every 24 h using mTSeR medium (Stemcell Technologies). Cell lines were passaged at a 1:6 ratio after 70-80% confluency using Dispase (Stemcell Technologies) and a cell scraper for gentle dissociation.…”
Section: Viral Titer Reduction Assaysmentioning
confidence: 99%
“…Indeed, many of the same molecular mechanisms governing both embryonic and adult lung progenitor cells and embryonic gene regulation networks can reappear in the adult lung pathologies, including cancer (21). Finally, it was pointed out that knowledge of the mechanisms that control embryonic lung development will provide a framework for driving the differentiation of iPSCs into lung progenitors (22).…”
Section: Clinicalmentioning
confidence: 99%
“…His studies demonstrated that dual inhibition of TGFb and BMP signaling after the formation of activin A-induced endoderm resulted in a highly enriched population of anterior foregut endoderm. Subsequent addition of Wnt3a, keratinocyte growth factor (KGF), FGF10, epidermal growth factor, and BMP4 to the culture induced cellular lineage differentiation toward an anterior ventral foregut phenotype (22). Subsequent screening of 400 culture conditions on the anterior foregut endoderm identified an optimal combination for the production of alveolar epithelial type II cells.…”
Section: Session 2: Embryonic Stem Cells Ipscs and Lung Regenerationmentioning
confidence: 99%
“…hESC-derived endoderm cells into hepatic progenitors (Touboul et al, 2010) SB431542 + CKI-7 ALK4,5 & 7 + Casein Kinase TGFb + LEFTYA Retinal (Osakada et al, 2009) SB431542 + NOGGIN ALK4,5 & 7 + BMP TGFb Neurogenesis (Chambers et al, 2009) Anterior Foregut Endoderm (Green et al, 2011) Endocrine differentiation from hESC-derived pancreatic progenitors SB431542 + Purmorphamine ALK4,5 & 7 + SHH TGFb + SHH Motor Neuron Precursors (Patani et al, 2009) …”
Section: Iwp-4 Iwr-1mentioning
confidence: 99%